A New Polymer Electron Acceptor Based on Thiophene‐S, S‐dioxide Unit for Organic Photovoltaics. Issue 2 (24th October 2017) - Meng, Bin; Miao, Junhui; Liu, Jun; Wang, Lixiang
Abstract: For polymer solar cells (PSCs), efficient polymer electron acceptors are always based on strong electron‐withdrawing imide unit or boron–nitrogen coordinative bond (B←N). In this paper, a new polymer electron acceptor based on thiophene‐ S, S ‐dioxide (TDO) unit is reported. The polymer electron acceptor, PBDT‐TDO, consists of alternating TDO unit and 4, 8‐bis(alkylthienyl)‐2‐yl]benzo[1, 2‐b:4, 5‐ b ′]dithiophene (BDT) unit. For comparison, a control polymer with alternating BDT unit and thiophene unit has also been synthesized. Replacing thiophene unit with TDO unit in the polymer backbone leads to large downshift of lowest unoccupied molecular orbital/highest occupied molecular orbital energy levels by 0.9 eV/0.4 eV, which is attributed to the dearomatization and electron deficiency of TDO unit. The replacement also leads to redshift of absorption spectra by ≈110 nm. PSC device with PBDT‐TDO as the electron acceptor shows photovoltaic response with the preliminary power conversion efficiency of 0.64%. This work suggests a new approach to design polymer electron acceptors using the TDO unit. Abstract : Replacement of the thiophene unit with thiophene‐ S, S ‐dioxide unit in the conjugated polymer backbone leads to downshift of lowest unoccupied molecular orbital/highest occupied molecular orbital energy levels by 0.91 eV/0.42 eV, respectively, and consequently transforms a typical polymer electron donor to electron acceptor.